An empirical study on the relationship between self-efficacy, employees’ creative performance, and thinking style in the Bangladeshi trade companies - Md. Mominul Islam; Sabrina Islam (Future Business Journal)
Abstract Purpose This study examines the relationship between self-efficacy, thinking style, and creative performance in Bangladeshi trade companies. Employee creativity is essential for organizational growth in competitive global markets. While self-efficacy has been researched in Western contexts, limited studies address its role in non-Western economies like Bangladesh. Research significance Prior studies often overlook the relationship between self-efficacy, thinking style, and job stressors, particularly in high-pressure work environments. This study addresses these gaps by examining how self-efficacy and thinking style contribute to creative performance and reassessing the role of job stressors in this dynamic. Methodology The research used a quantitative approach. Surveys were conducted with 300 employees, including 40 managers, managing directors, and chief operating officers from 40 Bangladeshi trade companies. Linear regression analysis tested the hypotheses, and additional analyses validated the relationships between key variables. Findings The results confirm that self-efficacy positively influences both thinking style and creative performance. Thinking style also significantly enhances employees’ creative performance. Contrary to initial expectations, job stressors do not moderate the relationship between self-efficacy and thinking style but emerge as significant independent predictors, highlighting their direct role in influencing cognitive processes. Contributions and novelty This study is among the first to integrate self-efficacy, thinking style, and job stressors in a non-Western trade sector. It offers an integrated framework for understanding how self-efficacy, and thinking style influence performance in trade companies. The study contributes to organizational behavior literature by examining these dynamics in Bangladesh’s trade sector. Implications The findings offer practical insights for managers in emerging economies. Managers should focus on building employee self-efficacy through targeted training. Promoting diverse thinking styles can further enhance creativity. These measures can improve employee creativity and organizational competitiveness.